IoT-Based Cigarette Smoke Monitoring System Using MQ135 Gas Sensor - Fitria, Fitria; Khalid, Anhar; Iryanie, Emy; Heldalina, Heldalina (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study develops an Internet of Things (IoT)-based monitoring system to detect cigarette smoke using the MQ135 gas sensor. Cigarette smoke is a major contributor to indoor air pollution and contains harmful chemical compounds that pose health risks to both active and passive smokers. The system integrates the MQ135 sensor with the NodeMCU ESP8266 microcontroller to collect air quality data and transmit it to an IoT platform for real-time monitoring. Testing results show that the MQ135 sensor responds quickly to changes in air quality, with PPM values increasing significantly when exposed to cigarette smoke compared to normal conditions. Data are displayed through a cloud-based dashboard and notification alerts are sent when pollutant levels exceed a predefined threshold. The findings indicate that the proposed system operates reliably and effectively, making it suitable for indoor environments to support smoke-free areas and improve air quality monitoring practices.